Human-Centered AI Literacy to Support Tolerance and Social Cohesion in a Diverse Community - Henoch Juli Christanto; Gallen Cakra Adhi Wibowo; Dita Madonna Simanjuntak; Manatap Dolok Lauro; Christine Dewi (Universitas Ahmad Dahlan, 2026)
Background: The growing use of generative AI in everyday learning and communication creates both opportunities and risks, including misinformation, bias, and unethical use, which may intensify social tension in diverse communities. This highlights the need for human-centered AI literacy that promotes not only technical use but also critical thinking, ethical awareness, and respect for differences. Contribution: This community service program addresses the gap in community-based AI literacy initiatives by integrating responsible generative AI use with tolerance education for socially vulnerable children in a diverse social setting. Method: A participatory one-day seminar and workshop were conducted on 14 June 2025 at Panti Asuhan Bersinar, East Jakarta. The program combined interactive instruction with guided hands-on practice using ChatGPT as a generative AI learning tool. Evaluation employed pretest-posttest assessment, Likert-scale questionnaires, facilitator observation, practice-based assessment, and short interviews. Results: The mean score increased from 46 in the pretest to 82 in the posttest, with an average n-gain of 0.7061, indicating high effectiveness. These findings suggest that the program effectively strengthened responsible AI literacy and reinforced ethical awareness relevant to tolerance and social cohesion. Conclusion: The integrated seminar-workshop model was effective in improving participants’ understanding of constructive, critical, and ethical AI use. This approach also shows potential as a replicable community-based strategy for promoting responsible AI literacy and social harmony in diverse settings.